Acute manipulation and real-time visualization of membrane trafficking and exocytosis in Drosophila. - Glashauser, J.; Camelo, C.; Hollmann, M.; Backer, W.; Jacobs, T.; Sanchez, J.I.; Schleutker, R.; Förster, D.; Berns, N.; Riechmann, V.; Luschnig, S. (Developmental Cell, 2023)
Intracellular trafficking of secretory proteins plays key roles in animal development and physiology, but so far, tools for investigating the dynamics of membrane trafficking have been limited to cultured cells. Here, we present a system that enables acute manipulation and real-time visualization of membrane trafficking through the reversible retention of proteins in the endoplasmic reticulum (ER) in living multicellular organisms. By adapting the "retention using selective hooks" (RUSH) approach to Drosophila, we show that trafficking of GPI-linked, secreted, and transmembrane proteins can be controlled with high temporal precision in intact animals and cultured organs. We demonstrate the potential of this approach by analyzing the kinetics of ER exit and apical secretion and the spatiotemporal dynamics of tricellular junction assembly in epithelia of living embryos. Furthermore, we show that controllable ER retention enables tissue-specific depletion of secretory protein function. The system is broadly applicable to visualizing and manipulating membrane trafficking in diverse cell types in vivo.